REVIEW: PEMBELAJARAN ORGANEL SEL PADA TUMBUHAN HYDRILLA VERTICILATA L - Astari, Milla; Mustakim, Ardi (Cahaya Ilmu Bangsa Institute, 2025)
Hyrilla verticillata, otherwise known as hydrilla, is a submersed aquatic plant that belongs to the Hydrocharitaceae family. This plant is characterized by stems that can grow up to 9 meters and leaves that are arranged in a whorl, 5-20 mm long and 0.7-2 mm wide. The hydrilla leaves have serrated edges and are often equipped with small spines along the midribs. This plant can reproduce vegetatively through fragmentation, as well as through turions and tubers which allow survival in unfavorable environmental conditions. Ecologically, hydrilla plays an important role in nutrient cycles and aquatic habitats, but can also be an invasive species that disrupts local ecosystems. Their rapid growth can reduce dissolved oxygen levels in the water, affecting fish populations and other organisms. In addition, hydrilla can also affect water quality by increasing pH and temperature. Even though it has benefits as a habitat for fish, its negative impact on biodiversity and human activities in waters makes managing this species a challenge for scientists and natural resource managers.